2003
DOI: 10.1093/ps/82.10.1550
|View full text |Cite
|
Sign up to set email alerts
|

Graded atmospheric oxygen level effects on performance and ascites incidence in broilers

Abstract: The effects of graded atmospheric O2 concentration (12, 14, 16, 18, and 20.6%) on chick performance and propensity to develop ascites were investigated using commercial male broilers. Chicks were housed in calorimetry chambers for 2 wk with incoming air diluted with N to provide the desired O2 concentration at thermoneutral (TN) ambient temperature. Day 14 body weight, weight gain, feed consumption, and gain-to-feed ratio increased (P < 0.01) as O2 concentration incrementally rose from 12 to 20.6%. Body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…Some researchers have suggested that extra O 2 supplementation during high-altitude incubation improves body weight, feed consumption and FCR (Beker et al, 2003;Quintana et al, 2006;Çelen et al, 2009) in 42-day-old broilers reared at low altitude. However, in the present study, at the end of the growing period, feed consumption and FCR were lower in the LA-NOX group than the HA ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have suggested that extra O 2 supplementation during high-altitude incubation improves body weight, feed consumption and FCR (Beker et al, 2003;Quintana et al, 2006;Çelen et al, 2009) in 42-day-old broilers reared at low altitude. However, in the present study, at the end of the growing period, feed consumption and FCR were lower in the LA-NOX group than the HA ones.…”
Section: Discussionmentioning
confidence: 99%
“…Growth increases the need for O 2 consumption (Beker et al, 2003), and rapidly growing broiler chickens need O 2 for their high metabolic requirements (Julian et al, 1989). As the O 2 level decreases with altitude, exposure to chronic hypoxia increases mortality during incubation and decreases growth as a result of adaptation (Julian, 2000;Villamor et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth, particularly which of lean tissue, increases the need for O 2 consumption [4]. Maxwell et al [22] and Witzel [18] concluded that BW at 8 weeks of age was correlated with embryonic O 2 consumption on day 14-19 of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Beker et al [3] demonstrated an inverse relationship between oxygen consumption and ascites incidence (R 2 = 0.96). Beker et al [4] found that final BW, BW gain, feed consumption and gain to feed ratio increased quadratically as the partial pressure of O 2 rose from 12% to 20.6%, while ascites heart ratio, ascites score, right ventricular mass and hematocrit increased as partial pressure of O 2 decreased. Additionally, Vander Hel et al [32] compared 1 d old chicks exposed to 15% O 2 with control birds exposed to 20.9% O 2 .…”
Section: Discussionmentioning
confidence: 99%